'C-type' closed state and gating mechanisms of K2P channels revealed by conformational changes of the TREK-1 channel. (11th January 2022) - Zhang, Qiansen; Fu, Jie; Zhang, Shaoying; Guo, Peipei; Liu, Shijie; Shen, Juwen; Guo, Jiangtao; Yang, Huaiyu
ABSTRACT: Two-pore domain potassium (K2P) channels gate primarily within the selectivity filter, termed 'C-type' gating. Due to the lack of structural insights into the nonconductive (closed) state, 'C-type' gating mechanisms remain elusive. Here, molecular dynamics (MD) simulations on TREK-1, a K2P channel, revealed that M4 helix movements induce filter closing in a novel 'deeper-down' structure that represents a 'C-type' closed state. The 'down' structure does not represent the closed state as previously proposed and instead acts as an intermediate state in gating. The study identified the allosteric 'seesaw' mechanism of M4 helix movements in modulating filter closing. Finally, guided by this recognition of K2P gating mechanisms, MD simulations revealed that gain-of-function mutations and small-molecule activators activate TREK-1 by perturbing state transitions from open to closed states. Together, we reveal a 'C-type' closed state and provide mechanical insights into gating procedures and allosteric regulations for K2P channels.